2009
DOI: 10.1097/aln.0b013e3181a06ec3
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Intraoperative Bacterial Contamination of Peripheral Intravenous Tubing Through the Use of a Novel Device

Abstract: Improved hand hygiene compliance through the use of a novel hand sanitation strategy reduces the risk of intraoperative bacterial transmission. The intervention was associated with a reduction in healthcare-associated infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
125
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(129 citation statements)
references
References 31 publications
1
125
0
2
Order By: Relevance
“…35,37,54,57 " 66 Counting devices can also be fitted into personal dispensers of ABHR worn on the body to increase convenience of hand hygiene. 67 In some studies, increased use of ABHR was associated with an increase in observed hand hygiene adherence; 68 " 71 however, not all studies have found such an association. 36,54,72 Automated dispenser counting systems may cost upward of $30,000-$40,000USD per patient care unit, and data must be manually downloaded from the counters if an automatic web-based download via Wi-Fi is not used.…”
Section: Methods For Hand Hygiene Adherence Measurementmentioning
confidence: 99%
“…35,37,54,57 " 66 Counting devices can also be fitted into personal dispensers of ABHR worn on the body to increase convenience of hand hygiene. 67 In some studies, increased use of ABHR was associated with an increase in observed hand hygiene adherence; 68 " 71 however, not all studies have found such an association. 36,54,72 Automated dispenser counting systems may cost upward of $30,000-$40,000USD per patient care unit, and data must be manually downloaded from the counters if an automatic web-based download via Wi-Fi is not used.…”
Section: Methods For Hand Hygiene Adherence Measurementmentioning
confidence: 99%
“…The standard precautions include hand washing, using personal protective equipments when likely to come into contact with bodily substances e.g. gloves, gowns, aprons, and eye goggles, correct and safe disposal of sharps, in addition to correct disposal and management of infectious waste (9,10,11) . Guidelines about infection control measures are one of the strategies that have used to prevent the spread of infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…As Loftus et al 2,3 and Koff et al 4 have demonstrated, preventing SSI involves attention to many facets of management. We have shown that small behavioral changes can easily decrease the contamination in our anesthesia environment.…”
Section: Discussionmentioning
confidence: 96%